Determinants of Stock Price : Fundamental Analysis on LQ45 Index Companies in Indonesia - Fauziah, Hana; Pebrian, Esa Lisa; Parlina, Nurhana Dhea (Research Collaboration Community (RCC), 2024)
The primary objective of this reserach was to examine the essential internal factors that affect stock prices by utilizing Return on Equity (ROE) and Dividend Payout Ratio (DPR) as independent variables, while Price to Book Value (PBV) was considered as an intervening variable. The focus of the study was on companies listed in the LQ45 index on the Indonesia Stock Exchange from 2018 to 2022. The data was analyzed using panel data regression through the REM, with support from Eviews 12 software. Path analysis was also employed to test hypotheses and gain deeper insights. The research findings indicate that only ROE significantly affects stock prices both directly and indirectly, while DPR doesnt have a significant influence on the fluctuations of stock prices. Additionally, PBV cannot mediate the effect of ROE and DPR on stock prices. This suggests that other factors can affect stock prices in the Indonesian capital market. It is crucial to consider a representative sample of companies and additional variables to gain deeper insight into the factors leading to share prices.